Pendampingan Penyusunan Pedoman Tata Kelola Satuan Pendidikan Swasta Dalam Rangka Implementasi Kebijakan Merdeka Belajar - Fatkhuri Fatkhuri (LPPM ITB AAS Indonesia Surakarta, 2023)
Education is a constitutional mandate in which its fulfilment becomes the responsibility of the government. With various limitations in resources, especially the budget owned by the government, the implementation and management of education have involved community participation through private educational institutions. This community involvement is carried out in the context of conducting studies carried out through the guidance of organizing private high schools in Indonesia. Private high schools in Indonesia are one of the educational institutions that play a significant role in the implementation of learning programs to educate all children in the nation. However, the arrangement of private schools has not received full attention from the government. Therefore, there are no standardized benchmarks for private schools, resulting in a wide variation in the facts and dynamics of education in the field. The guidance program for organizing private high schools is an important initiative to conduct a study to find the best governance model for private high schools in Indonesia. A focus on financial management patterns (planning, implementation, and supervision) of private high schools needs to be conducted to establish standardized education practices. Accordingly, the government can intervene accurately and measurably to support more effective future implementation of private high school education.